Catalyst free, one-pot, facile synthesis of novel pyrazolo-1,4-dihydropyridine derivative form pyranopyrazoles - Sohal, Harvinder Singh; Goyal, Arun; Khare, Rajshree; Singh, Kishanpal; Sharma, Rajeev (European Journal of Chemistry, 2014)
One pot synthesis of pyrazolo-1,4-dihydropyridine derivatives from pyranopyrazoles using acidic solvent system is described. The targeted molecules were obtained in good to excellent yield without the use of expensive catalysts, toxic solvents and chromatographic separation. The generality and functional tolerance of this convergent and environmentally benign method is demonstrated.